Obstacles and Solutions in Performing Islamic Financial Contracts - Hoetoro, Arif (Ekonomi Syariah IAIN Kudus, 2018)
There are some obstacles faced by Islamic microfinance institutions in performing Islamic financial contracts as purely demanded by Islamic law. In case of Bayt al-Maal wa al-Tamweel (BMT), the application of Islamic financial contracts needs a special approach and innovation. By taking BMT Sidogiri of East Java as the research site, this study qualitatively evaluated the practice of murabahah, mudlarabah, and musharakah contracts conducted by such an insti-tution. In examining these obstacles, this study had conducted several in-depth interviews with the branch manajer of BMT Sidogiri of Malang City. The findings revealed that the obstacles in performing Islamic financial contracts are dominated by lack of knowledge, asymmetric information, limited cooperation among related institutions, opportunistic behavior, and lack of social capital. To overcome these obstacles, it is recommended that the practices of Islamic financial transactions were not only in line with shari’ah-compliant but also with shari’ah-based schemes.